Cardiovascular Efficacy and Safety of Bococizumab in High-Risk Patients - Ridker, Paul M; Revkin, James; Amarenco, Pierre; Brunell, Robert; Curto, Madelyn; Civeira, Fernando; Flather, Marcus; Glynn, Robert J; Gregoire, Jean; Jukema, J Wouter; Karpov, Yuri; Kastelein, John J P; et al. (The New England journal of medicine, 2017)
BACKGROUND: Bococizumab is a humanized monoclonal antibody that inhibits proprotein convertase subtilisin-kexin type 9 (PCSK9) and reduces levels of low-density lipoprotein (LDL) cholesterol. We sought to evaluate the efficacy of bococizumab in patients at high cardiovascular risk. METHODS: In two parallel, multinational trials with different entry criteria for LDL cholesterol levels, we randomly assigned the 27,438 patients in the combined trials to receive bococizumab (at a dose of 150 mg) subcutaneously every 2 weeks or placebo. The primary end point was nonfatal myocardial infarction, nonfatal stroke, hospitalization for unstable angina requiring urgent revascularization, or cardiovascular death; 93% of the patients were receiving statin therapy at baseline. The trials were stopped early after the sponsor elected to discontinue the development of bococizumab owing in part to the development of high rates of antidrug antibodies, as seen in data from other studies in the program. The median follow-up was 10 months. RESULTS: At 14 weeks, patients in the combined trials had a mean change from baseline in LDL cholesterol levels of -56.0% in the bococizumab group and +2.9% in the placebo group, for a between-group difference of -59.0 percentage points (P<0.001) and a median reduction from baseline of 64.2% (P<0.001). In the lower-risk, shorter-duration trial (in which the patients had a baseline LDL cholesterol level of ≥70 mg per deciliter [1.8 mmol per liter] and the median follow-up was 7 months), major cardiovascular events occurred in 173 patients each in the bococizumab group and the placebo group (hazard ratio, 0.99; 95% confidence interval [CI], 0.80 to 1.22; P=0.94). In the higher-risk, longer-duration trial (in which the patients had a baseline LDL cholesterol level of ≥100 mg per deciliter [2.6 mmol per liter] and the median follow-up was 12 months), major cardiovascular events occurred in 179 and 224 patients, respectively (hazard ratio, 0.79; 95% CI, 0.65 to 0.97; P=0.02). The hazard ratio for the primary end point in the combined trials was 0.88 (95% CI, 0.76 to 1.02; P=0.08). Injection-site reactions were more common in the bococizumab group than in the placebo group (10.4% vs. 1.3%, P<0.001). CONCLUSIONS: In two randomized trials comparing the PCSK9 inhibitor bococizumab with placebo, bococizumab had no benefit with respect to major adverse cardiovascular events in the trial involving lower-risk patients but did have a significant benefit in the trial involving higher-risk patients. (Funded by Pfizer; SPIRE-1 and SPIRE-2 ClinicalTrials.gov numbers, NCT01975376 and NCT01975389 .).
Keywords: Treatment Failure; protilátky; Male; Cholesterol, LDL; neúspěšná terapie; Middle Aged; PCSK9 inhibitory; Risk Factors; proproteinkonvertasa subtilisin/kexin typu 9; Hypercholesterolemia; hypercholesterolemie; LDL-cholesterol; následné studie; mužské pohlaví; Follow-Up Studies; humanizované monoklonální protilátky; dvojitá slepá metoda; Antibodies, Monoclonal, Humanized; kardiovaskulární nemoci; lipidy; Antibodies; lidé; ženské pohlaví; Proprotein Convertase 9; Humans; anticholesteremika; rizikové faktory; Anticholesteremic Agents; Lipids; Cardiovascular Diseases; Double-Blind Method; Female; PCSK9 Inhibitors; lidé středního věku; Injections, Subcutaneous; injekce subkutánní